Motivations regarding continuing or terminating pregnancy in women with high-risk pregnancies: a scoping review - Antunes, Mónica (2025)
Background: The decisions of women with high-risk pregnancies to continue or terminate a pregnancy are complex and influenced by various factors. This scoping review synthesises the qualitative literature on the underlying motivations influencing these decisions. Aim: This analysis explores the underlying motivations that influence women's decisions regarding the continuation or termination of pregnancy, considering the challenges and dilemmas this population faces. Methods: This review was conducted following the Joanna Briggs Institute's methodology. No date restrictions were applied to the search. Titles and abstracts were screened to select original studies, and cross-checking was performed to avoid case overlap. We included studies that focused on the factors influencing women's decisions to either continue or terminate pregnancies when complications arose. Results: Eighteen studies involving women from different countries and cultural contexts were included. The review identifies four main themes driving these decisions: health considerations, religious convictions, social and political factors and ethical and moral dilemmas. Each theme interlinks to form a complex web of influences that significantly shape women's choices, illustrating how deeply personal, societal, and ethical contexts converge in these critical decisions. Significant emotional and cognitive factors, particularly hope, also play a crucial role. The findings highlight the complexity of the decision-making process and provide a deeper understanding of the personal, social, and spiritual dimensions involved. Conclusions: Multiple factors shape the complex decisions of women with high-risk pregnancies. Understanding these motivations is crucial to providing appropriate support and counselling. This review underscores the need for healthcare professionals to be aware of the diversity of factors involved and to adopt an individualized and context-sensitive approach in their practice, guiding their future actions.